2021
DOI: 10.3390/s21217408
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Iris Presentation Attacks Using Feature Fusion of Thepade’s Sorted Block Truncation Coding with Gray-Level Co-Occurrence Matrix Features

Abstract: Iris biometric detection provides contactless authentication, preventing the spread of COVID-19-like contagious diseases. However, these systems are prone to spoofing attacks attempted with the help of contact lenses, replayed video, and print attacks, making them vulnerable and unsafe. This paper proposes the iris liveness detection (ILD) method to mitigate spoofing attacks, taking global-level features of Thepade’s sorted block truncation coding (TSBTC) and local-level features of the gray-level co-occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The study by [8] states that combining TSBTC and GLCM can increase detection accuracy. The TSBTC and GLCM are used to form the feature vectors of iris images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study by [8] states that combining TSBTC and GLCM can increase detection accuracy. The TSBTC and GLCM are used to form the feature vectors of iris images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deep CNN models have been employed in recent facial liveness identification studies because they provide more accurate liveness detection than the previously presented strategies [7,8,14,15]. For facial anti-spoofing detection, Atoum et al suggested a twostream CNN-based method that included a patch-based CNN and a depth-based CNN [25].…”
Section: Deep Learning-based Facial Anti-spoofing Approachesmentioning
confidence: 99%
“…A facial spoofing attack is an attempt by an unauthorized person to circumvent the facial authentication protocol and the facial verification process by employing deception techniques, such as identity forgery [5]. A printed image of an authorized face or a recorded video from a display may provide sufficient unique data to deceive the system [6,7]. As a result, the resiliency of these security systems can be diminished.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the iris having a distinct textural structure, the imposter might falsify it [7]. Table 1 shows the iris presentation attacks used that are found in the literature [8].…”
Section: Introductionmentioning
confidence: 99%